2015
DOI: 10.1016/j.knee.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet versus no tourniquet on knee-extension strength early after fast-track total knee arthroplasty; a randomized controlled trial

Abstract: Tourniquet versus no tourniquet on knee-extension strength early after fast-track total knee arthroplasty; a randomized controlled trial.Harsten, Andreas; Bandholm, Thomas; Kehlet, Henrik; Toksvig-Larsen, Sören Link to publication Citation for published version (APA): Harsten, A., Bandholm, T., Kehlet, H., & Toksvig-Larsen, S. (2015). Tourniquet versus no tourniquet on kneeextension strength early after fast-track total knee arthroplasty; a randomized controlled trial. Knee, 22(2), 126-130. DOI: 10.1016/j.knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 27 publications
(28 reference statements)
7
49
0
2
Order By: Relevance
“…However, the results of the latter study are difficult to interpret because of possible under-powering and because the patients were not blinded [31]. Other studies have reported a better effect on either ROM [15] or 2 or more rehabilitation-related outcome measures, including ROM, pain, SLR, swelling, and ADL function, when a tourniquet is either not used or is used for only a short period [1014, 1619].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the latter study are difficult to interpret because of possible under-powering and because the patients were not blinded [31]. Other studies have reported a better effect on either ROM [15] or 2 or more rehabilitation-related outcome measures, including ROM, pain, SLR, swelling, and ADL function, when a tourniquet is either not used or is used for only a short period [1014, 1619].…”
Section: Discussionmentioning
confidence: 99%
“…In the fast-track cohort of TKR the use of a tourniquet was less common, but the influence of a tourniquet on functional outcome is inconclusive according to previous studies (Ledin et al 2012, Zhang et al 2014, Harsten et al 2015, Zhou et al 2017. Ledin et al (2012) showed in a small randomized study an improved range of motion (ROM) persisting after 2 years and Harsten et al (2015) showed no effect regarding postoperative pain and muscle strength when a tourniquet was not used while Zhang et al (2014) and Zhou et al (2017) found a better ROM in early stage after surgery when not using a tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that long-term use of tourniquet can reduce intraoperative and intraoperative total blood loss, while short-term use of tourniquet can reduce postoperative and postoperative hidden blood loss without increasing the rate of allogeneic blood transfusion [23]. Interestingly, some studies found that 48 h after total knee arthroplasty, the strength of knee extension was not superior in the group without tourniquet, but tourniquet caused lower limb pain [24,25]; others suggested that the use of tourniquet had no signi cant correlation with postoperative rehabilitation [26]. In summary, studies on tourniquet use or not have been reported, but there is little literature comparing postoperative rehabilitation with limited tourniquet use versus no tourniquet use.…”
Section: Discussionmentioning
confidence: 99%